Application of MCSFilter to estimate stiction control valve parameters - Amador, Andreia (2020)
The mitigation of the stiction phenomena in control valves is of paramount importance for efficient industrial plant operation. Mathematical models of sticky valves are typically discontinuous and highly nonlinear. A derivative-free optimization method is applied in the context of parameter estimation in order to determine the stiction parameters of a control valve. The method successfully determines the correct parameter set and compares favorably with a previous case study of this problem that used smooth function.